DNA directed immobilization enzyme on polyamidoamine tethered magnetic composites with high reusability and stability. Issue 35 (17th August 2016) - Song, Jiayi; Su, Ping; Yang, Ye; Wang, Ting; Yang, Yi
Abstract : A novel enzyme immobilization procedure was developed. The immobilized enzyme composites exhibited significantly improved digestion performance, excellent reusability, stability and dynamic reversible reproducibility. Abstract : The development of new strategies for stabilizing or improving the activities of enzymes has attracted considerable interest because of the wide range of potential applications and high cost of the native enzymes. In this study, a novel trypsin immobilization procedure in which the enzyme was immobilized using polyamidoamine (PAMAM) dendrimer modified magnetic nanoparticles as carriers through DNA-directed immobilization was developed for the first time. The optimal DNA base pairs and the optimal generation of PAMAM on the enzymatic activity were 24 bases and G3.0PAMAM, respectively. The trypsin binding capacity of the immobilized trypsin was 74.6 mg g −1, and the K m and V max values were 1.23 mM and 468.35 μmol min −1 mg protein −1, respectively. The immobilized trypsin reactor exhibited excellent reusability and stability properties without significant loss in enzymatic activity. Notably, the high level of enzymatic activity remained at more than 63% after 82 cycles, with only a slight decrease (above 88%) after 14 weeks of continuous use at one-week intervals. The high reversibility and reproducibility of this trypsin dynamic immobilization strategy were also investigated. The significantly improved digestion performance of the immobilized trypsin composites was further demonstrated by digesting cytochrome C, myoglobin and glycated hemoglobin, with sequence coverages of 78%, 99% and 88%, respectively, which were higher than those obtained for the free enzyme. This system therefore shows great potential in high throughput enzymatic assays and proteome analysis.